‘WHO HAS GOT WHAT’: The political economy of land conflict in local development - Abdullah, Sait; Ramdhani, Deni F.; Iyoega, Rofi’ R.; Ismail, Solahuddin Bin (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
This paper explores the political economy angels entail in the land conflict between the government and the local people. Land conflict between the government and the local people has been popular phenomenon in Indonesia. In the case of the local government in Indonesia, particularly in the Bandung City development, previous researchers have studied this issue by investigating the conflict either through institutional approach or people perspective.  However, have they failed to investigate the political and economic aspects inherent in the land conflict. This political economy dimension is missing from their studies.  By using the political economy approach proposed by Hughes and Hutchison who understand the material and political dimensions underlying the land conflict, the study contributes to the debate on studies of the land conflict.  The political economy aspect is important in unrevealing the economic and political reasons behind the surface of the conflict. In Investigating the phenomenon, the research uses qualitative method by interviewing the people of Tamansari area, the government officials, and the civil society organization. The research findings suggests that the political economy aspect is useful in understanding and mapping the political economy actors involved. The political economy perspective also contributes to the Bandung City Government in making the local government aware to the interests of the wider community, especially those affected by the conflict.gb777